Generation of two isogenic iPSC lines from a healthy male donor of European ancestry - S. Edwards; L. Hagenau; B. Nowack; J. Rhode; M.F. Hossain; A. Tzvetkova; L.R. Jensen; A.W. Kuss (Stem Cell Research, 2024)
We have created two isogenic iPSC lines from fibroblasts of a healthy male donor of European ancestry. The cell lines express common pluripotency markers, are free of chromosomal aberrations and are able to differentiate into cells of all three germ layers. These iPSC are now a resource for genome editing with the aim of creating models of genetic disorders without having to depend on patient cells.